ISLAM, PANCASILA AND VALUE SYSTEMS OF INDONESIAN NATIONAL EDUCATION - Beck, DR. Martha Catherine; Irawan, Irawan (Jurnal Pendidikan Islam, 2016)
This paper intends to show that the Pancasila (five principles of state) and the Pillars of Islam (the five religious value system) has synergy to build Indonesia's national education values system. To explore the relation between religion and politics in Pancasila, Martha Beck used Alfred North Whitehead's process philosophy, Carl Gustav Jung's archetypes psychology and Ervin Laszlo‟s systems theory. To approve that Pancasila and Pillars of Islam has synergy to Indonesia‟s national education, Irawan used the concept of scientia sacra by Seyyed Hossein Nasr. The results showed that the Indonesian national education system consistently present in a triangular relationship between religion (spiritual humanism), politics (democracy) and cultural (multicultural and tolerance). The relationship manifested in Indonesian National Education System, which is always grounded philosophically and aims at three things; 1) form human who believe, cautious and has noble character; 2) master of science and technology; and 3) actively participate in creating order and peace in the world, even a blessing for the entire universe. Indonesia's national education system could be a new alternative in building a more holistic education systems around the world because considered crucial interconnection between science, religion, interests of state and demands of the global. This is known as a moderate Islamic education.